PERGESERAN GENDER PADA INTERIOR RUMAH TINGGAL DI KAWASAN JERON BENTENG YOGTAKARTA - Dwi Nugroho, Martino (Lintas Ruang: Jurnal Pengetahuan dan Perancangan Desain Interior, 2008)
One of the instruments incorporated for the construction of social reality is gender Javanese society traditionally embraces social concept of patriarchy The general Implication is that woman becomes a man s subordinate Broader implementation also can be comprehended fromdissociation of social activities and rituals involving both men and women Viewed fromthespatial perspective there are differences between man space and woman space This is based on the research conducted in Jeron Beteng an area in the city of Yogyakarta The analysis has resulted what follows 1 the sittingroom shows a friction once mastered by man now it turns into equation with indicators equal status ownership custom affection domestic duty execution and sittingroom domination influencing factors modernization attitude and emancipation respect 2 the livingroom also demonstrates a friction once a woman domaintoday it is accessible to man as well influencing factors  communication marital status age work emancipation modernization moral and formal education and foreign culture 3 the kitchen witnesses an equal role for a woman and man regarding domestic duty openness and communication Woman however remains to be more dominant in kitchen although men have access in there influencing factors communications age work emancipation modernization moral and formal educationKeywords : gender interior sitting room livingroom kitchen